2004
DOI: 10.1162/1063656043138914
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Linkage Discovery by Limited Probing

Abstract: This paper addresses the problem of discovering the structure of a fitness function from binary strings to the reals under the assumption of bounded epistasis. Two loci (string positions) are epistatically linked if the effect of changing the allele (value) at one locus depends on the allele at the other locus. Similarly, a group of loci are epistatically linked if the effect of changing the allele at one locus depends on the alleles at all other loci of the group. Under the assumption that the size of such gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 12 publications
1
65
0
Order By: Relevance
“…A learning method not based on statistical independence tests has been investigated by Heckendorn and Wright (2004). Earlier work has been reported by Munetomo and Goldberg (1999).…”
Section: Sample Complexity For Learning the Adf Structure By Probingmentioning
confidence: 99%
“…A learning method not based on statistical independence tests has been investigated by Heckendorn and Wright (2004). Earlier work has been reported by Munetomo and Goldberg (1999).…”
Section: Sample Complexity For Learning the Adf Structure By Probingmentioning
confidence: 99%
“…Two previous algorithms for linkaged iscoveryu sed the same randomized test for linkage asused in this paper [4,7], but instead ofusingb inary search restricted each instance of the test to detect linkage between a specific pair of positions i and j , resulting in a requirement 2 …”
Section: Overview Of the Algorithmmentioning
confidence: 99%
“…Previous work has shown that additively separable problems of order k defined on strings of length M can be solved using Ο (2 k M 2 ) function evaluations [4,7] 1 , 2 . Empirical evidence as well as facetwise decompositional models suggest that sub-quadratic ( Ο (2 k M β ) for β < 2) performance is possible.…”
Section: Introductionmentioning
confidence: 99%
“…values of the variables one by one. These interactions among variables immanent in problems is called linkage [13,9] or epistasis [10,4,20].…”
Section: Introductionmentioning
confidence: 99%
“…In the approaches, the epistasis among variables are implicitly estimated and applied to the evolution of solutions. Recently, a number of approaches that attempt to detect independently optimizable linkage groups of a pseudo-Boolean function 1 have been proposed [13,9,23]. The Walsh transform, first introduced by Bethke [2] and popularized by Goldberg [7,8], is one of the classical methods for analyzing epistatic properties of a pseudo-Boolean function.…”
Section: Introductionmentioning
confidence: 99%